Assessing offshore wind farm collision risks using AIS data: An overview - Jürgen Weigell; Carlos Jahn (Changing Tides: The New Role of Resilience and Sustainability in Logistics and Supply Chain Management – Innovative Approaches for the Shift to a New Era. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 33, 2022)
Purpose: Currently offshore wind farms are built in areas with high vessel traffic like the German Economic Exclusive Zone (EEZ). During the building phase and the operational phase a high amount of vessels will pass these offshore wind farms in close proximity and thus there is a risk of collision of a vessel with other vessels in the wind farms, e.g. installation vessels or service vessels or with objects like the wind turbines or the substation of an offshore wind farm. Methodology: In this paper relevant publications over the last ten years with a focus on the use of AIS (Automated Identification System) in regard to the collision risks of offshore wind farms will be investigated and sorted in a structured way. The publications will then be listed and classified into six sub groups. Findings: This analysis will show an overview of the current state of the art in using AIS data to determine the collision risks for offshore wind farms and the proposed methods to reduce these risks. Originality: The paper is original because there is currently no complete and up-to-date overview for the use of AIS-data to mitigate the collision risks.
urn:nbn:de:gbv:830-882.0201048; hdl:10419/267179; https://econpapers.repec.org/RePEc:zbw:hiclpr:33
Keywords: 650; Maritime Logistics